Karakteristik Teori Komunikasi dalam Penyiaran TVRI Medan untuk Membangun dan Menjaga Budaya di Sumatra Utara - Hotmatua Paralihan; Nisrina Ardra Hafizha; Afrini Yuninda Silitonga; Elisa Damayanti; Dwi Arlintang; Susan Ramadhani; Irhamna (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
North Sumatra is rich in cultural diversity, and television broadcasting can be an effective means of connecting and strengthening the community's cultural identity. This research explores the characteristics of communication theory in TVRI Medan broadcasting as an effort to build and strengthen cultural groups in North Sumatra. Using the free interview method with the Head of the Production Section of TVRI Medan in the context of a study visit to the UIN SU Communication Science study program to TVRI Medan. This research also uses library research methods, namely by using various literature in the form of books, scientific works, and national and international journals. This research focuses on the analysis of cultural broadcast programs, namely, Pesona Indonesia as a concrete case study. The results show that communication theory was successfully implemented through collaboration between broadcast communication theory and intercultural communication theory by looking at actual social reality. The implications of these findings provide practical guidance for the development of culture-based broadcasting programs